Clarithromycin added to bortezomib‐cyclophosphamide‐dexamethasone impairs health‐related quality of life in multiple myeloma patients. (29th October 2018) - Nielsen, Lene Kongsgaard; Klausen, Tobias Wirenfeldt; Jarden, Mary; Frederiksen, Henrik; Vangsted, Annette Juul; Do, Trung; Kristensen, Ida Bruun; Frølund, Ulf Christian; Andersen, Christen Lykkegaard; Abildgaard, Niels; Gregersen, Henrik
Abstract: Objectives: The Danish Myeloma Study Group initiated a randomized, placebo‐controlled, double‐blinded phase II study to investigate the efficacy of adding clarithromycin to cyclophosphamide‐bortezomib‐dexamethasone (VCD) induction therapy in transplant eligible, newly diagnosed multiple myeloma patients. The study was prematurely terminated due to severe complications, and no effect of adding clarithromycin was found. The aim of this study was to compare health‐related quality of life (HRQoL) between the two groups and to explore the coherence hereof with adverse event (AE) registration by clinicians. Methods: Patients completed three validated HRQoL questionnaires at inclusion, before cyclophosphamide priming, and two months after high‐dose therapy (HDT). The mean score difference was interpreted by clinically relevant differences between groups. Spearman's correlation analysis was used to compare patient‐reported toxicities with AEs. Results: Of 58 included patients, 55 participated in the HRQoL reporting. Before cyclophosphamide priming, patients in the clarithromycin group reported clinically relevant reduced HRQoL for eleven domains with persistent reduction in four domains two months after HDT. Poor correlation between patient‐reported toxicities and clinician‐reported AEs was observed. Conclusions: Despite the premature study termination, our data demonstrate impaired HRQoL when clarithromycin was added to the VCD regimen. We found clear underreporting of toxicities by clinicians. ClinicalTrials.gov number NCT02573935.